MODEL BAHAYA BANJIR MENGGUNAKAN DATA PENGINDERAAN JAUH DI KABUPATEN SAMPANG (FLOOD HAZARD MODEL USING REMOTE SENSING DATA IN SAMPANG DISTRICT) - Nanik Suryo Haryani; Any Zubaidah; Dede Dirgahayu; Hidayat Fajar Yulianto; Junita Pasaribu (Indonesian National Institute of Aeronautics and Space (LAPAN), 2012)
Flood is the first biggest disaster in Indonesia, as stated by the National Disaster Management Agency (BNPB) in the BNPB’s natural disaster data of year 2000 to 2009. Considering the flood has the significant impact of causing the casualties and material losses, it is necessary to study on it. One of useful data for studying the flood is remote sensing data. The advantage of good historical data makes it possible to see the changes of cover/land use from year to year in a region. The extensive area coverage of remote sensing data allows it to view and analyze in a comprehensive manner. The method of the study of flood hazard models is using multiple variables, where each variable has a class of criteria. Determination of the weight of each flood variable by using the Composite Mapping Analysis. The results of this study shows the main cause of flooding in the District of Sampang is that most of the land system in the cities are the combined estuary and swamp plain, forming a low land and is triggered by the torrential rain. The model of flood hazard maps produced by variable weighting floods with a multi criteria analysis method which is function of rainfall, landuse, slope, land system and elevation. Key words: Flood hazard, Composite Mapping Analysis, Remote sensing